Retrospective analysis of leflunomide and low-dose methylprednisolone for the treatment of diabetic nephropathy combined with membranous nephropathy - Shang, Shunlai; Cui, Shaoyuan; Wang, Wenjuan; Wang, Chao; Li, Ping; Li, Wenge; Li, Qinggang (Frontiers in Endocrinology, 2022)
Abstract：Diabetic kidney disease (DKD) combined with Membranous Nephropathy (MN) was observed in some patients with the increasing of Diabetic patients. However, no treatment guidelines are available for DKD combined with MN. In this study, we for the first time analyzed the safety and efficacy of leflunomide (LEF) combined with low-dose glucocorticoid methylprednisolone (MP) in the treatment of DKD with MN. We retrospectively collected clinical data related to patients with the highest number of DKD combined with MN diagnosed by renal biops between December 2016 and December 2020. The inclusion criteria were a history of diabetes for more than 20 months, no glucocorticoid therapy or immunosuppressant therapy for at least 6 months, urine protein greater than 3.5 g, and a follow-up time of 16 months. On top of conservative treatment, the patients received LEF monotherapy (LEF, n = 38) or LEF combined with low-dose methylprednisolone (LEF+MP, n = 26). After 16 months of treatment, the complete remission rate was 2.6%, the remission rate was 15.8% in the LEF group; for the LEF+MP group, the complete remission rates and the remission rate were 23.1% and 34.6%, respectively. At month 16, urine protein was lower than the baseline value in both groups (p < 0.05) and was significantly lower in the LEF+MP group than in the LEF group (p < 0.05). Serum albumin was higher than the baseline value in both groups (p < 0.05), with no significant between-group difference (p > 0.05). No inter- or intragroup difference was observed in serum creatinine or glycated hemoglobin. During treatment, the relapse rate was lower in the LEF+MP group than in the LEF group (p < 0.05). No irreversible adverse event was observed. In a word, LEF+MP is more effective than LEF monotherapy for DKD combined with MN. Large, long-term, randomized, double-blind, controlled studies are needed to further validate the clinical efficacy of LEF+MP.